Navigating TEFL Graduate Students Challenges and Strategies in Utilizing Critical Thinking Skills in Thesis Writing - Ibnu Habibi; Nunung Fajaryani; Reli Handayani (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
Thesis writing is a difficult procedure that requires critical thinking skills. Thus, one of the challenges that many students face while writing a thesis is the development of critical thinking skills during the writing process. The purpose of this study is to investigate the challenges and strategies that graduate students at Universitas Jambi face while trying to develop their critical thinking skills when writing theses. The researchers used case study method since the issue that were analyzing at was one particular case at Universitas Jambi's Master of English Education. To acquire the data, the researcher used interviews methods. The findings revealed that there were several challenges faced by the students in utilizing critical thinking when writing thesis. Those challenges include personal competence, linguistic, and psychological factors. In addition, the students employ some strategies to cope with the challenges arised in applying critical thinking skills when writing thesis. It includes time-management, technological support, reading and sources evaluation, and support system.